Testing The Warrants Mispricing and Their Determinants: The Panel Data Models - Muhammad Rizky Prima Sakti; Abdul Qoyum (Global Review of Islamic Economics and Business, 2017)
This paper empirically studied the impact of several variables such as moneyness, stock return, maturity, and volatility on the warrant mispricing. We selected 4 companies listed in Bursa Malaysia such as MHC Plantations Bhd, MKH Bhd, YFG Bhd, and UNISEM to investigate the mispricing of warrants. Subsequently, panel time series data employed with daily basis from 30 June 2010 until 30 June 2013. The Black-Scholes Option Pricing Model (BSOPM) used to determine the mispricing of warrant. Several panel data techniques employed in this study such as pooled-OLS, fixed effect model (FEM), and random effect model (REM). In turn, we found that FEM is well explained the determinants of warrant mispricing. Thus, empirical results suggest that moneyness, maturity, and volatility are positively and significantly explained the mispricing of warrant, while stock return does not give an impact toward the warrant mispricing. The BSOPM is consistently mispricing the warrant either in-the-money (ITM) or out-the money (OTM) warrants. The market is not efficient on the warrants traded for four companies observed